Feminist epistemology after postmodernism: Critiquing science, technology and globalisation - Braidotti, Rosi (Interdisciplinary Science Reviews, 2007)
This article provides a reasoned overview of contemporary developments within feminist theories of the subject after the decline of postmodernist thought. It stresses the foundational importance of feminist situated epistemology, and hence of a brand of materialism that stresses embodiment and embedded perspectives. The article explores neo-materialist feminist theories in a number of areas, with special emphasis on science and technology studies and critiques of globalisation. It argues that the neo-materialist trend results in a new call for an ethics attuned to the complexity of our era.
Keywords: approches et analyses; bio-technologie; discipline; environnement; féminisme matérialiste; philosophie; postmodernisme; projet charge mentale; ressource en ligne; sciences humaines; thématiques; épistémologie

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme